2005
DOI: 10.1111/j.1365-2249.2005.02960.x
|View full text |Cite
|
Sign up to set email alerts
|

A form of circulating interleukin-6 receptor component soluble gp130 as a potential interleukin-6 inhibitor in inflammatory bowel disease

Abstract: SummaryThe presence and the role of soluble gp130, the soluble form of a component of the interleukin (IL)-6 receptor complex, were investigated in inflammatory bowel disease. The serum concentrations of soluble gp130 were increased in ulcerative colitis (active disease, median, 93·5 ng/ml; interquartile range, 26-125 ng/ml; inactive disease, 81 ng/ml, 24·8-137·3 ng/ml) and to a lesser extent in Crohn's disease (active disease, 66 ng/ml, 44·4-87·6 ng/ml; inactive disease, 63 ng/ml, 43·5-82·5 ng/ml) compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Solid arrows represent the effects of cholinergic agonists on IL-6 mediated signaling components and downstream events. support the role of nicotine as a regulator of the JAK2/STAT3/ SOCS3 signaling pathway in inflammatory bowel disease (38).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Solid arrows represent the effects of cholinergic agonists on IL-6 mediated signaling components and downstream events. support the role of nicotine as a regulator of the JAK2/STAT3/ SOCS3 signaling pathway in inflammatory bowel disease (38).…”
Section: Discussionmentioning
confidence: 98%
“…For example, IL-6, STAT3, and SOCS3 have been implicated in inflammatory bowel disease (1,17,39,46) and soluble gp130 has been shown to suppress inflammatory bowel disease (38). Inflammatory bowel disease is a condition that can be treated with the cholinergic agonist nicotine experimentally (59) and clinically (14,16,44,52), as well as with anti-IL-6R antibody (24).…”
Section: Discussionmentioning
confidence: 98%
“…IL-6R shedding is therefore an active process within this condition, and sIL-6R required for IL-6-dependent gp130 activation is most likely released either by lamina propria macrophages or infiltrating neutrophils [57,87]. Interestingly, it was recently reported that not only levels of IL-6 but also levels of sIL-6R and sgp130 are elevated in chronic inflammatory bowel diseases and that IL-6 found in the circulation was complexed to sIL-6R and sgp130 [95].…”
Section: Il-6 Trans-signaling In Colitis and Colon Cancermentioning
confidence: 96%
“…Increased levels of IL-6, sIL-6R, and soluble gp 130 (sgp130), have been reported in IBD. Thus, the IL-6 trans-signaling pathway may play an important role in the pathogenesis of IBD (Mitsuyama et al 2006b). Studies in CD and experimental colitis have shown that inhibition of IL-6 trans-signaling suppresses T cell resistance to apoptosis, indicating that the IL-6-sIL-6R system mediates the resistance of T cells to apoptosis in CD (Atreya et al 2000;Kallen 2002).…”
Section: CDmentioning
confidence: 98%